INTERNATIONAL EXPERIENCE OF IMPLEMENTING NEW PUBLIC ADMINISTRATION MODELS - Levchenko S.O. (Pressing Problems of Public Administration, 2017)
Research into the results of the leading international practices of public participation in publicprocesses has been conducted.